MENGGALI KEARIFAN LOKAL NUSANTARA MELALUI INTEGRASI ISLAM, SAINS, DAN BUDAYA: PERSPEKTIF HISTORIS ERA WALISONGO - Fikri, Muslim; Roqib, Mohammad (PABKI (Perkumpulan Ahli Bimbingan dan Konseling Islam) Indonesia, 2023)
This journal tries to investigate the complexity of integration between Islam, science and Indonesian culture in the Walisongo era. This research explores the roots of local Indonesian wisdom by examining the central role of Walisongo in integrating these three aspects into community life. Through careful historical analysis, this journal reveals how the Walisongo era became the starting point for the formation of a unique cultural identity in the archipelago. The approach used in this research is a qualitative approach, with the type of library research. The results of this research illustrate the interaction between religious beliefs, scientific knowledge, and cultural heritage shaping Indonesian society in this historical period. This study provides in-depth insight into the important role of Walisongo in integrating Islamic values, science and local traditions which ultimately form the foundation of a rich and diverse culture in the archipelago.